A non‐normative account of assertion. (22nd August 2018) - Black, Dylan
Abstract: Many contemporary philosophers argue that assertion is governed by an epistemic norm. In particular, many defend the knowledge account of assertion, which says that one should assert only what one knows. Here, I defend a non‐normative alternative to the knowledge account that I call the repK account of assertion. According to the repK account, assertion represents knowledge, but it is not governed by a constitutive epistemic rule. I show that the repK account offers a more straightforward interpretation of the conversational patterns and intuitions that motivate the knowledge account. It does so in terms of ordinary normative principles that philosophers already accept, none of which are constitutive to assertion. I then contend that the repK account is preferable to the knowledge account because it is simpler, its implications are less contentious, and it avoids a problem for normative accounts of assertion recently raised by Peter Pagin. I also argue that the repK account offers a satisfying explanation of selfless assertion, a counterexample to the knowledge account posed by Jennifer Lackey.